تطوير مواد الإملاء على أساس المعرفة بالمحتوى التربوي التكنولوجي (TPACK) لترقية مهارة الكتابة لدى الطلبة في المدرسة المحمّدية المتوسطة سيدوموليو كوالا مادو - Kastrawi, Puji; Taufiqur Rochman; Nur Hasaniyah (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2025)
Writing is one of the most in-demand skills today. Writing skills in Arabic are divided into three parts: calligraphy, imla' and insya'. The research methodology used is an experimental development approach with quantitative and qualitative approaches. Data collection methods include interviews, observations, questionnaires and tests. The result of this research and development is that imla' material was developed based on TPACK using the ADDIE model which consists of 1) Analysis: The most basic problem after conducting interviews and observations is the lack of textbooks to teach imla'. 2) Design: The researcher identified the teaching materials of imla' in the book about connecting the letters hijaiyah, tanwin, alif lam syamsiyyah and qamariyah, ta' marbuthah and maftuhah, and hamzah. Development: consists of cover, book data, introduction to the imla' book, guide to using the book, contents, imla' materials, exercises, providing material videos for each chapter through barcodes, providing dictation exercises through barcodes, research resources. 4) Implementation: Held at Muhammadiyah Sidomulyo Kwala Madu Junior High School. 5) Evaluation: through design experts and materials as well as student exam results. The development of this imla' material is different from previous research because it adds and integrates technology in the imla' material.